2021
DOI: 10.1111/acfi.12764
|View full text |Cite
|
Sign up to set email alerts
|

Financial reporting and corporate innovation: a review of the international literature

Abstract: We synthesise the empirical studies on innovation in the accounting, finance, and corporate governance disciplines using Bushman and Smith's corporate transparency framework as our theoretical lens. The review presents competing findings on the association between financial reporting and innovation. Most of the reviewed studies fail to address the critical question of how the financial reporting system affects the interactions among financial development, corporate governance and innovation. We suggest future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 192 publications
(235 reference statements)
0
5
0
Order By: Relevance
“…The average values of AGE suggest that the over- and under-investment firms were listed on the SET for approximately 26 years. Comparable to the evidence of Huang et al (2021), the average values of LOSS suggest that 22.6% of underinvestment firms and 14.9% of overinvestment firms reported loss performance. The mean values of PRO are 0.082 and 0.067 for overinvestment and underinvestment, respectively, and these profitability ratios are identical to those of Chinese firms reported by He et al (2022).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The average values of AGE suggest that the over- and under-investment firms were listed on the SET for approximately 26 years. Comparable to the evidence of Huang et al (2021), the average values of LOSS suggest that 22.6% of underinvestment firms and 14.9% of overinvestment firms reported loss performance. The mean values of PRO are 0.082 and 0.067 for overinvestment and underinvestment, respectively, and these profitability ratios are identical to those of Chinese firms reported by He et al (2022).…”
Section: Resultsmentioning
confidence: 62%
“…It is expected that those conflicts will be more pronounced among firms in innovation-targeted industries. In comparison to noninnovative firms, innovative firms have a faster rate of innovation and a shorter life cycle of products or services, which makes market participants require high-quality financial information to predict growth (Huang et al , 2021). Financial reporting quality (FRQ) was found to be associated with the number of patents (Park, 2018) and optimal investment in market-oriented economies (Li and Wang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al. [2021a] found that both the quantity and quality of patents are positively correlated with voluntary management forecasts and internal information quality. Our analysis could help clarify these seemingly inconsistent empirical findings.…”
Section: Empirical Implicationsmentioning
confidence: 99%
“…Furthermore, [35] examines the impact of corporate governance on company performance during the COVID-19 pandemic, suggesting that companies with good corporate governance practices, such as board independence and CEO-chair separation, were better able to navigate the pandemic and maintain their financial performance. [36] investigates the relationship between corporate governance and company performance in China during the COVID-19 pandemic, finding that good corporate governance practices, such as board independence and audit committee effectiveness, are associated with better company performance. The board of directors plays a crucial role in corporate governance.…”
Section: Literature Review and Theoretical Framework Underpinning The...mentioning
confidence: 99%